PENERAPAN MODEL PROBLEM BASED LEARNING BERBANTUAN GAMES PANCASILA ADVENTURE UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS SISWA KELAS IV SD - Ilahiyah Wahyuni, Niswatin; Julianto; Ceffiriana, Paramita; Wiludjeng, Sri; Hidayati, Fitria (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
In an effort to realize learning success, teachers must choose models and methods that suit the material and students' abilities. One of the students' abilities that can create active learning is the ability to think critically. This classroom action research aims to improve the critical thinking skills of class IV students at SDN Pagesangan by implementing the Problem Based Learning (PBL) learning model assisted by the Pancasila Adventure game. The data obtained is based on the results of observations and tests. Data analysis was carried out using descriptive techniques. The research subjects were 29 grade IV students at SDN Pagesangan, including 17 female students and 12 male students. The results of research in cycle I showed that students' critical thinking abilities were in the high category 6.90%, in the medium category 31.04%, in the low category 51.72% and in the very low category 10.34%. In cycle II, it showed that critical thinking skills increased with a very high category of 17.24%, a high category of 68.97%, a medium category of 10.34%, and a low category of 3.45%. Thus, it can be concluded that by implementing the PBL (Problem Based Learning) learning model with the help of the Pancasila Adventure game, it can improve students' critical thinking skills in class IV Pancasila Education learning at SDN Pagesangan.